Examen Especial al Rubro Inventarios en la Empresa Comercial “Acabados del Austro” de la Ciudad de Loja, período 2021. - Bermeo Ojeda, Jhulissa Gabriela (2023)
We developed the curricular integration work entitled Special Examination to the Inventory Item in the Commercial Company "Acabados del Austro" of the city of Loja, period 2021, to comply with the objectives set out in this research paperwork as; evaluate the internal control system implemented by the commercial company "Acabados del Austro" for the management and control of the inventory item to determine the efficiency and effectiveness; determine the reasonableness of the balances of the inventory line item presented in the respective financial statements of the entity; and prepare the report containing comments, conclusions and recommendations of the findings established as a result of the Special examination, including the opinion on the reasonableness of the balances of the inventory line item. Among the main findings encountered, it is determined as a result that the commercial company "Acabados del Austro" does not perform monthly physical inspections; it has not established written regulations or a manual of functions detailing the functions and responsibilities of each of the individuals working in the company; It does not have daily control of the products; it does not have enough space in the warehouse for the merchandise; it does not assign a single person to control the inventories, and there are no internal regulations. With this background in mind, we made recommendations as alternatives for the betterment of the company to achieve the goals and objectives proposed by the company.